Β-Cypermethrin promotes the adipogenesis of 3T3-L1 cells via inducing autophagy and shaping an adipogenesis-friendly microenvironment. (8th July 2020) - He, Bingnan; Wang, Xia; Jin, Xini; Xue, Zimeng; Zhu, Jianbo; Wang, Caiyun; Jin, Yuanxiang; Fu, Zhengwei
Abstract: The toxicity of synthetic pyrethroids has garnered attention, and studies have revealed that pyrethroids promote fat accumulation and lead to obesity in mice. Nevertheless, the effect of β-cypermethrin (β-CYP) on adipogenesis and its underlying mechanism remains largely unknown. In this study, mouse embryo fibroblasts 3T3-L1 cells were exposed to β-CYP, and the cell viability, intracellular reactive oxygen species (ROS) level, autophagy, and adipogenesis were assessed to investigate the roles of oxidative stress and autophagy in the toxic effects of β-CYP on adipogenesis. The results demonstrated that treatment with 100 μΜ β-CYP elevated the ROS level, decreased mitochondrion membrane potential, stimulated autophagy, and enhanced the adipogenesis induced by the mixture of insulin, dexamethasone, and 3-isobutyl-1-methylxanthine. However, co-treatment with N -acetyl-L-cysteine partially blocked the abovementioned effects of β-CYP in 3T3-L1 cells. In addition, co-treatment with rapamycin, an autophagy agonist, enhanced the inductive effect of β-CYP on adipogenesis, whereas co-treatment with 3-methyladenine blocked the enhancement of adipogenesis caused by β-CYP. Moreover, β-CYP also altered the microenvironment of 3T3-L1 cells to an adipogenesis-friendly one by reducing the extracellular expression of miR-34a, suggesting that the culture media of β-CYP-treated 3T3-L1 cells could shift macrophages to M2 type. Taken together, the data obtained in the present study demonstrated that β-CYP promoted adipogenesis via oxidative stress-mediated autophagy disturbance, and it caused macrophage M2 polarization via the alteration of miR-34a level in the microenvironment. The study demonstrated the adipogenesis-promoting effect of β-CYP and unveiled the potential mechanism.